PENGARUH SERTIFIKASI TERHADAP KINERJA GURU MELALUI KOMPETENSI DAN DISIPLIN KERJA (STUDI KASUS PADA SMK NEGERI KOTA MAKASSAR) - Herman Jelatu; Ulmi Azary Ramdani (Pojok Publisher, 2024)
The role of teachers cannot be separated from the achievement of national education goals, because success in education is closely related to their contribution. Teachers play an important role in determining the quality of education in Indonesia. This research aims to determine the effect of certification on teacher performance through competence and work discipline at SMKN in Makassar City. This research uses quantitative methodology. The population in this research is teachers at SMK Negeri Makassar who have been certified as many as 100 teachers. Data collection using questionnaires, observation and documentation, with data analysis methods involving descriptive analysis and path analysis. The results of the analysis obtained findings that; 1) certification has a real impact on teacher competence; 2) certification has a real impact on teacher competence; 3) certification has a real impact on teacher performance; 4) competence has a real impact on teacher performance; 5) work discipline has a real impact on teacher performance; 6) competence can mediate the effect of certification on teacher performance; 7) work discipline plays a role in mediating the impact of certification on teacher performance at SMKN in Makassar City.